Significados e sentidos dos discursos de um grupo de crianças da 3ª série do ensino fundamental sobre a profissão e os gêneros na docência - CHARONE, Tatiana do Socorro Pacheco (2008)
This research investigates the meanings and senses of the speeches of a group of children of the 3rd year of elementary school upon the profession and the genders in the teaching, with the intention of analyzing through the children's speeches the unfoldings of the gender issues in the educational work and in the teaching. The children were my speakers and subjects in this work and their voices were my research object and analysis. The discursive approach was the perspective adopted in the investigation process. The instruments used in the collection of the data were semi-structured interviews and the use of two photographic images adopted as starting points of the dialogue with the children. The research was accomplished at a school of the municipal public net of Ananindeua-PA, and in the educational staff of this school, there were 19 female teachers and 08 male teachers working from the 1st to 4th years at the time of the investigation. The theoretical referential used as contribution for the analysis of the data collected is based on Mikhail Bakhtin's theories on the speech. In order to relate the children's voices with the social, cultural and historical contexts lived by them, we used authors such as Aries, Perrot, Connell, Carvalho, Louro. The analyses were organized in 05 thematic axis which emerged from the children's speeches: 01 - The ideological speeches about the educational profession and the historical definition of roles and functions for the sexes; 02 - The meaning of the profession and its historical and cultural bonds with the maternity; 03 - Manhood and Femininity: The multiples senses attributed to the genders in the teaching; 04 - Power relationships between adults and children and in the educational practice; 05 - The exercise of the teaching and the affective relationships. The children's speeches demonstrate a lot of continuities and also ruptures with the roles which were historically built for men and women. The main sense of the feminine teaching for the children is in the attention and patience and of the masculine teaching it is in the authority. Their speeches also present a lot of expectations and wishes for the teaching practice which overcomes binarisms and polarities and which offer significant information so as we can (re)think the teaching.